Effects of tie detailing configurations on reinforcement buckling and seismic performance of high-strength RC columns. Issue 147 (August 2021) - Wu, Dianqi; Ding, Yang; Su, Junsheng; Li, Zhong-Xian; Zong, Liang; Feng, Keyan
Abstract: The premature buckling and subsequently low-cycle fatigue fracture of longitudinal bars is one of the main failure modes of reinforced concrete (RC) columns under earthquake loading. The use of high-strength steel bars (HSSB) in RC columns reduces rebar diameter or increases tie spacing, thus increases the vulnerability of bar buckling. In view of this, this paper studies the effects of transverse reinforcement detailing (referred hereafter also as 'tie detailing') configurations on reinforcement buckling and then on the seismic performance of high-strength RC columns. Five rectangular RC columns with different tie detailings and axial load ratios were tested under constant axial load and reversed horizontal load. All three tie detailings studied have the same large rectangle closed-hoop, while small hoops/ties are different: including two cross-ties (Type Ⅰ), a small rhombus closed-hoop (Type Ⅱ), or two small rectangle closed-hoops (Type Ⅲ). The axial load ratio includes 0.06 and 0.18. The anti-buckling constraint mechanisms of different tie detailings are proposed, and then the global buckling length of longitudinal bars in RC columns with different tie detailings are calculated. On this basis, the effects of tie detailing on bar buckling and on the seismic performance of RC columns are studied. The observed results of bar buckling verify the reliability of the proposed anti-buckling constraint mechanisms and reinforcement buckling length calculation model. Type Ⅲ tie detailing provide better anti-buckling constraint, and thus reduces buckling length of longitudinal bars of RC columns than that with Type Ⅰ & Type Ⅱ tie detailings. Meanwhile, the use of Type Ⅲ tie detailing enhances the seismic performance of RC columns (ultimate drift ratio and hysteretic dissipated energy) than that with Type Ⅰ & Type Ⅱ tie detailings. The effects of tie detailing on seismic performance of RC columns are more significant under high axial load ratio. As the longitudinal bars are more susceptible to buckle under high axial compression, thus Type Ⅲ tie detailing can more prominently play its advantages of delaying bar buckling and improving the seismic performance of RC columns. Highlights: Experimentally study the effects of tie detailing on seismic performance of high-strength RC columns. Propose anti-buckling constraint mechanisms of different tie detailings. Verify the reliability of anti-buckling constraint mechanisms and buckling length calculation model by experiments. Tie detailing influences bar buckling and then the seismic performance of RC columns. Effects of tie detailing on seismic performance of RC columns are more significant under high axial load.